2021
DOI: 10.1016/j.amsu.2021.102877
|View full text |Cite
|
Sign up to set email alerts
|

Effect of erythropoietin administration on expression of mRNA brain-derived Neutrophic factor, levels of stromal cell-derived Factor-1, and neuron specific enolase in brain injury model Sprague Dawley

Abstract: Background Traumatic brain injury (TBI) is a complicated condition that is the primary cause of death and disability in children and young adults in developed countries. Various kinds of therapy have been carried out in the management of brain injury, one of which is the administration of erythropoietin (EPO). There are not many studies in Indonesia have proven that EPO administration is effective on parameters such as stromal cell-derived factor 1 (SDF-1), brain-derived neurotrophic factor (BDNF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…C-EPO is a derivative of erythropoietin that has shown tissue-protective effects on the brain, heart, and other tissues following various types of injuries [4]. However, the effects of C-EPO on lung function in sepsis-induced injury and the underlying mechanisms remain to be fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…C-EPO is a derivative of erythropoietin that has shown tissue-protective effects on the brain, heart, and other tissues following various types of injuries [4]. However, the effects of C-EPO on lung function in sepsis-induced injury and the underlying mechanisms remain to be fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that EPO was able to reduce brain edema at 1 and 4 days after TBI ( Blixt et al, 2018 ). The neuroprotective function was elicited by increasing the mRNA brain-derived neurotrophic factor expression and serum SDF-1 levels within 24 h after TBI in rats ( Said et al, 2021 ). In addition, a novel strategy was developed to load EPO with Tween 80-modified albumin nanoparticles using electrostatic spray technology.…”
Section: Epo Treatment In Tbimentioning
confidence: 99%